Promising research studies between mathematics literacy and financial literacy through project-based learning - Sagita, Laela; Putri, Ratu Ilma Indra; Zulkardi; Prahmana, Rully Charitas Indra (Journal on Mathematics Education, 2022)
Financial literacy is a knowledge and attitude about finance and is a 21st-century skill. As a knowledge, a cognitive factor of a person will impact their financial literacy skill. Through a bibliometric analysis study of 274 documents published from 1994 to 2022 in the Scopus database, we found that mathematics literacy is the cognitive factor of one's financial literacy skill. The OECD and several studies offer intertwined concepts, financial literacy and mathematics, to be presented in the mathematics curriculum in primary and secondary schools. After we got the bibliometric results, we surveyed several junior high schools in Yogyakarta to learn more about this issue. A total of 15 mathematics teachers participated in this survey, randomly chosen in junior high school. We got information stating that mathematics teachers used financial terms as a social arithmetic context, did not teach financial knowledge and attitudes, and never heard 13 from 17 financial terms in the survey. Furthermore, we present a framework for implementing financial literacy in mathematics through three dimensions, content, context, and process. The dimension content consists of mathematics' and financial content. On the other hand, the dimension context is related to education and work, home and family, and individual and societal. As a cognitive process, the dimensions of the process are based on Bloom's Cognitive stages. The potential for future research is developing learning activities and implementing them in the independent curriculum, which impacts schools' ability to use project-based learning, which is the most approach to implementing financial literacy in mathematics classes.